Healthy weight, health behaviours and quality of life among Aboriginal children living in regional Victoria. (19th July 2022) - Browne, Jennifer; Becker, Denise; Orellana, Liliana; Ryan, Joleen; Walker, Troy; Whelan, Jill; Alston, Laura; Egan, Mikaela; Johnson, Brittney; Rossignoli, Amy; Crooks, Nicholas; Brown, Andrew D.; et al.
Abstract: Objective : To report the prevalence of healthy weight and related behaviours among Victorian Aboriginal and non‐Aboriginal children and explore associations between these factors and health‐related quality of life (HRQoL). Methods : Analysis of cross‐sectional data from two cluster randomised controlled trials using logistic and linear mixed models. The sample included Aboriginal (n=303) and non‐Aboriginal (n=3, 026) children aged 8–13 years. Results : More than two‐thirds of Aboriginal children met guidelines for fruit (75.9%), sweetened drinks (66.7%), sleep (73.1%), screen time (67.7%) and objectively measured physical activity (83.6%); and 79.1% reported consuming take‐away foods less than once per week. Aboriginal children were more likely to meet vegetable consumption guidelines (OR=1.42, 95%CI: 1.05, 1.93), but less likely to have a healthy weight (OR=0.66, 95%CI: 0.52, 0.85) than non‐Aboriginal children. Mean HRQoL scores were significantly higher among non‐Aboriginal children and both Aboriginal and non‐Aboriginal children meeting health guidelines. Conclusions : Most Aboriginal children in this study met guidelines for fruit, physical activity, screen time and sleep, and those meeting these guidelines had significantly higher HRQoL. Implications for public health : Promoting nutrition, physical activity and sleep is likely to benefit all children. Aboriginal community‐controlled organisations can use these data to design culturally‐specific programs that may improve disparities in healthy weight and HRQoL.